Awareness about Hospital Waste Management System Among Janitorial Staff in Public and Private Hospitals of Hyderabad a Comparative Analysis - Mahmood, Khalid; Ahmed, Farah; Ashraf, Viqar; Satti, Luqman (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess and compare the knowledge, attitude and practices of janitorial staff regarding the hospital waste management system in public and private hospitals of Hyderabad. Study Design: Comparative cross-sectional study. Place and Duration of Study: Public and Private Hospitals of Hyderabad, from Oct 2017 to Mar 2018. Methodology: All 47 male and female janitorial staff of private and 47 public hospitals, aged 18 years were given a semistructured questionnaire about knowledge, attitude and practices regarding healthcare waste management. Scoring adequate knowledge, positive attitude and good practices were done to draw the results. Results: Out of the 94 included, 62 were male, and 32 were females. The majority of workers, 52 (55%), had working experience <5 years, whereas 27 (29%) and 15 (16%) of workers had working experience of >10 years and between 5-10 years, respectively. In most of the knowledge and attitude-related questions, scoring of adequate knowledge and positive attitude was significantly higher in staff working in private than in the public hospital. In contrast, the scoring of practice-related questions was found to be significantly higher in staff working in a public hospital compared to those working in a private hospital. Conclusion: Knowledge, Attitude and Practices among janitorial staff working in public and private hospitals were not up to the mark and were not following the standard operative procedures while handling the healthcare waste. Hospital administration to formulate and implement refresher comprehensive training programs for the janitorial staff.